The Immunohistochemical Study of Stathmin-1 as A Prognostic Factor In Non-small cell Lung Carcinoma - Wetwet, Nadhema B.; Kerbel, Hadeel A.; Baay, Ali S.; Al-Obaidy, Muhammed W. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: The cell cycle progression and cell motility are mainly controlled by a major microtubule depolymerising protein called Stathmin1 (also known as metablastin). Stathmin1 has been found to be up-regulated in some cancers and correlated with cell differentiation and proliferation. Objectives: To evaluate the role of immunohistochemical expression of stathmin1 in non-small lung carcinoma and its correlation to different prognostic factors or parameters. Materials & Methods: This retrospective study carried on 50 cases of small lung carcinomas (surgical specimens of lung tumours embedded in formalin-fixed paraffin). Applying the immunohistochemical techniques by using the primary antibodies to Stathmin1. Statistical analysis was done, and an assessment of correlation with different clinical and pathological parameters was measured. Results: The results revealed Fifty cases of non-small lung carcinomas were subgrouped as 42% adenocarcinoma, 44% squamous cell carcinoma, 10%adeno-squamous,s and 4% non-small lung carcinoma , 84 % were Stathmin-1 positive, but there is nostatisticaly correlation between Stathmin-1 expression with age and patients’ gender but Stathmin-1 expression correlated with parameters including type and grade of tumor. High expression was noted in poorly differentiated tumours. Conclusion: From these results, we conclude that measurement of stathmin1 may be a beneficial prognostic biomarker for lung tumours, those poorly differentiated tumours. Stathmin1 expression in non-small cell lung carcinoma significantly correlated with poor tumor differentiation and could be considered an independent prognostic factor